ANALISIS POLA HUBUNGAN MODAL SOSIAL DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) SEBAGAI PENOPANG KINERJA PRODUKSI PADA KARYAWAN BAGIAN PRODUKSI KOPERASI SERBA USAHA BROSEM KOTA BATU - Lutvi Haviludin Najib; Elfia Nora (STIE Kesuma Negara Blitar, 2015)
This study aims to analyze the pattern of social capital relationships with its third pillars: confidence (trust), social networking, and social norms which can cause additional and voluntary behavior conducted outside the employee's role and duty called as Organizational Citizenship Behavior (OCB) as the support of production performance. In addition, this study also addressed how systems work and the characteristics of the employees can form a higher social capital so that employees will often show positive behavior (OCB) which appears on the aspects of altruism, courtesy, conscientiousness, civic virtue, and sportsmanship. This research is carried out on groups of production employees at KSU Brosem Batu as Koperasi Serba Usaha that produces Apple Cider “BOSEM”. This study uses modal analysis with its three pillars: trust, social networking and social norms that occurred in the group of employees that will be the existence of social capital which can foster a positive attitude within the organization that can encourage individuals to behave in order to achieve production targets. This study uses a qualitative case study approach. The results of this study indicate that social capital has a pattern of relationships with Organizational Citizenship Behavior (OCB). The higher sense of trust, social networks and the norms of the group of employees, the employees will often unwitting display of OCB in the group. Extra behavior conducted by employees can raise awareness to always help each other and work together, which in turn creates work productivity. The existence of this relationship, it is suggested that social capital is able to move the of the group effectively to encourage positive behavior for desired organization in the achievement of organizational goals at KSU Brosem that is productivity. Keywords: Social Capital, OCB, KSU Brosem